The influence of Ceres on the dynamical evolution of the Zdenekhorsky/Nemesis asteroid family - Carruba, V. [UNESP]; Barletta, W. [UNESP] (Elsevier, 2019)
The Nemesis family, also identified as the Zdenekhorsky family by some authors, is an “incomplete” asteroid family in the central main belt, characterized by an asymmetric distribution between its left and right side, with most of its members located in the left part of the family. It has been suggested that this asymmetry, as well as the shape of its left slope, could have been significantly affected by Ceres, either though close encounters or because of the effect of the nodal linear resonance ν1C. Several age estimates were also found for this family, ranging from a minimum of 150 ± 80 Myr to a maximum of 440 ± 20 Myr. Here we study the effect that Ceres may have had on the dynamical evolution of this family. For this purpose, we performed several numerical simulations that include the Yarkovsky effect and either consider or neglect Ceres as a massive body. We found that the asymmetric shape of this family does not seem to be a product of the local dynamics, but may be an intrinsic feature of the original ejection velocity field by which this family was created. If we assume that the current population of asteroids in librating states of the ν1C secular resonance is currently in a steady-state and originates from the Nemesis family, this population will no longer be sustainable on timescales of 200 Myr since the group formation, which sets an upper limit on the maximum possible family age.
Keywords: Asteroids: general-Minor planets; Asteroids: individual: (128) Nemesis, (3827) Zdenekhorsky, -Celestial mechanics; Minor planets